Sensores eletroquímicos à base de nanomateriais carbonáceos e catalisadores biomiméticos para determinação de tetraciclina em diferentes tipos de amostras - Scontri, Mateus [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work describes the preparation and feasibility of electrochemical sensors based on carbonaceous nanomaterials and biomimetic catalysts of the P450 enzyme, in order to obtain sensitive and selective sensors for determination of tetracycline. For this, electrochemical sensors were initially constructed using carbon paste modified with 10% (w/w) of MWCNTCOOH (carbon nanotubes multi-walled functionalized with carboxyl groups) and 10% (w/w) of graphene oxide (GO). Differential pulse with adsorptive anodic stripping voltammetry (DPadSAV) provided the best results in phosphate buffer 0.1 mol L-1 (pH 7.0) and accumulation potential and time of 0,2 V and 30 s, respectively. Under these conditions the sensor showed a linear response range between 1.2 x 10-5 and 1.7 x 10-4 mol L-1, sensitivity of 1.2 x 104 (± 1,0 x 103) A mol L-1 and detection limit of 3.6 x 10-8 mol L-1. This sensor has been applied to the determination of tetracycline in synthetic urine, river water and pharmaceutical formulations with recovery values close to 100% and repeatability in terms of relative standard deviation (RSD) below 6%. In the second stage of the work in order to obtain a biomimetic sensor, in addition to the nanoparticulate materials, carbon pastes were individually modified, with 11 organometallic compounds that mimic the active site of P450 enzyme. Among them, only bis(pyridil)phthalocyanine iron (II); 5,10,15,20-tetraphenyl-21H, 23H-porphyrin iron (III) chloride and 1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro-29H,31H-phthalocyanine cobalt (II) showed promising response using cyclic voltammetry. However, when performed experiments by VPD and DPadSAV in optimized conditions, none of the sensors showed satisfactory resposes, despite the efforts made to achieve the quantification of tetracycline. viii Showing that in this case, the these compounds did not improve the sensor response previously obtained...

Este trabalho descreve a preparação e viabilidade de sensores eletroquímicos à base de nanomateriais carbonáceos e catalisadores biomiméticos da enzima P450, visando à obtenção de sensores sensíveis e seletivos para determinação de tetraciclina. Para tal, inicialmente foram construídos sensores eletroquímicos usando pasta de carbono modificada com 10% (m/m) de MWCNT-COOH (nanotubos de carbono de paredes múltiplas funcionalizados com grupos carboxila) e 10% (m/m) de óxido de grafeno (GO). A Voltametria de pulso diferencial adsortiva com varredura anódica (VPDadVA) permitiu obter melhores resultados em solução tampão fosfato 0,1 mol L-1 (pH 7,0); potencial e tempo de acumulação de 0,2 V e 30 s, respectivamente. Sob estas condições o sensor apresentou uma faixa linear de resposta entre 1,2 x 10-5 e 1,7 x 10-4 mol L-1, sensibilidade de 1,2 x 104 (±1,0x103) μA mol L-1 e limite de detecção de 3,6 x 10-8 mol L-1. Este sensor foi aplicado na determinação de tetraciclina em urina sintética, águas de rio e medicamentos, obtendo-se recuperações com valores próximos a 100% e valores de repetibilidade em termos do desvio padrão relativo (DPR) abaixo de 6%. Na segunda etapa do trabalho, visando à obtenção de um sensor biomimético, além dos materiais nanopartículados, as pastas de carbono foram individualmente modificadas, com 11 compostos organometálicos que mimetizam o sitio ativo da enzima P450. Dentre eles, apenas a bispiridilftalocianinaferro (II), cloreto de 5,10,15,20-tetrafenil-21H,23H-porfirinaferro (III) e 1,2,3,4,8,9,10,11,15, 16,17,18,22,23,24,25-hexadecafluoro-29H,31H-ftalocianinacobalto (II) apresentaram resposta promissora usando voltametria cíclica. Entretanto, quando realizados experimentos de quantificação através de VPDadVA nas condições otimizadas, vi nenhum dos sensores mostrou respostas satisfatórias, apesar dos esforços realizados para conseguir a...
Keywords: Quimica analitica; Tetraciclina; Materiais carbonaceos; Materiais biomiméticos; Nanotubos de carbono; Carbonaceous materials